Graphene dispersion

A graphene dispersion with specific surface area and impurity control addresses the performance issues of conventional graphene dispersions, ensuring high output and cycle characteristics in lithium-ion batteries by uniform distribution and low viscosity.

JP2024176001APending Publication Date: 2024-12-19MITSUBISHI PENCIL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023094176
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-07
Publication Date
2024-12-19

AI Technical Summary

Technical Problem

Conventional graphene dispersions for battery electrodes, such as lithium-ion batteries, suffer from insufficient capacity retention rates at high C rates, high output, and long life (cycle characteristics), and have issues with dispersion in electrode slurries, leading to inadequate performance.

Method used

A graphene dispersion with a BET specific surface area of at least 15 m²/g to 70 m²/g, a 2D/G Raman spectroscopy peak height ratio of 0.3 to 0.9, and a total Fe, Co, and Ni content of 5000 ppm or less, combined with a dispersant and solvent, is used to achieve uniform dispersion and low viscosity, facilitating high output and cycle characteristics.

Benefits of technology

The graphene dispersion enables uniform distribution of conductive agents and active materials, maintaining high output and cycle characteristics without adversely affecting battery performance, thus enhancing the efficiency of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176001000001
    Figure 2024176001000001
  • Figure 2024176001000002
    Figure 2024176001000002
Patent Text Reader

Abstract

To provide a graphene dispersion suitable for manufacturing electrodes for batteries, including lithium-ion batteries.SOLUTION: A graphene dispersion for battery electrodes contains: a graphene material having a BET specific surface area of 15 m2 / g or more and less than 70 m2 / g, a peak height ratio of the 2D band to the G band (2D / G) by Raman spectroscopy of 0.3 or more and less than 0.9, and a total Fe, Co, and Ni content of less than 5000 ppm; a dispersant; and a solvent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a graphene dispersion suitable for producing battery electrodes for lithium ion batteries and the like. [Background technology]

[0002] With the spread of electric vehicles and the miniaturization, weight reduction, and improved performance of portable devices such as mobile phones and notebook personal computers, there is a demand for secondary batteries with high energy density, as well as for the secondary batteries with higher output and longer life. Under these circumstances, non-aqueous secondary batteries, including lithium-ion batteries using non-aqueous electrolytes, have come to be used in many devices due to their features of high energy density and high voltage, and their development is being actively carried out.

[0003] In the past, research has been conducted into the use of conductive materials such as acetylene black and carbon nanotubes (CNTs) in electrodes that constitute non-aqueous secondary batteries, including lithium-ion batteries, in order to reduce the resistance of the electrode material. However, it is well known that acetylene black requires a certain amount (e.g., 4% by mass of the active material) relative to the active material, making it difficult to increase the energy density and insufficient for high output. In addition, although the amount of CNT required relative to the active material is small (e.g., 0.1 to 1% by mass of the active material), iron and cobalt derived from the catalyst used to synthesize CNTs are mixed in as impurities, and there are currently many issues in terms of extending the life of the CNTs.

[0004] In recent years, graphene has been attracting attention as a next-generation conductive material, and many technologies have been disclosed. For example, Patent Document 1 describes "a dispersion comprising a solvent, graphene carbon nanoparticles having an average aspect ratio of greater than 3:1 and a Raman 2D:G peak ratio of at least 1:1, and a polymeric dispersant resin comprising an addition polymer containing residues of vinyl heterocyclic amide."

[0005] Patent Documents 2 and 3 disclose carbon materials in which graphite is dispersed in water in the presence of polyethylene glycol and sodium carboxymethylcellulose, and then the polyethylene glycol is removed at high temperature to exfoliate the graphite, thereby improving the function as a conductive material.

[0006] However, the graphene dispersion of Patent Document 1 above has an insufficient capacity retention rate at a high C rate and is still unsatisfactory in terms of increasing power and extending life (cycle characteristics), and the carbon materials of Patent Documents 2 and 3 above are still insufficient in dispersion when applied to an electrode slurry or the like, and similarly have an insufficient capacity retention rate at a high C rate and are still unsatisfactory in terms of increasing power and extending life (cycle characteristics), so there are currently problems. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2022-521587 A (Claims, Examples, etc.) [Patent Document 2] Patent No. 6641538 (Claims, Examples, etc.) [Patent Document 3] Patent No. 7164517 (Claims, Examples, etc.) Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention seeks to solve the above-mentioned problems in the related art, and has an object to provide a graphene dispersion that is useful for producing battery electrodes such as highly efficient lithium ion batteries. [Means for solving the problem]

[0009] As a result of extensive research into the above-mentioned conventional problems, the present inventors have found that 2 / g or more 70m 2The inventors have found that by dispersing, together with a dispersant, a graphene material having a BET specific surface area of ​​less than 100 nm / g, a peak height ratio of the 2D band to the G band (2D / G) of 0.3 to less than 0.9 as measured by Raman spectroscopy, and a total content of Fe, Co, and Ni of less than 5000 ppm, a graphene dispersion useful for the above-mentioned purpose as a battery electrode, etc., can be obtained, and have completed the present invention.

[0010] That is, the graphene dispersion of the present invention has a particle size of at least 15 m 2 / g or more 70m 2 The graphene material has a BET specific surface area of ​​less than 1 / g, a peak height ratio of the 2D band to the G band (2D / G) measured by Raman spectroscopy of 0.3 to less than 0.9, and a total content of Fe, Co, and Ni of less than 5,000 ppm, a dispersant, and a solvent.

[0011] The graphene material is preferably at least one selected from raw materials such as scaly graphite particles, flaky graphite particles, spherical graphite particles, expanded graphite particles, exfoliated expanded graphite particles, exfoliated scaly graphite particles, graphene particles, etc., and is subjected to a pulverization / classification procedure and a demetallization procedure as necessary. Effect of the Invention

[0012] The graphene dispersion of the present invention disperses a graphene material uniformly and has a low viscosity, so that coating for forming an electrode can be easily performed. According to the present invention, it is possible to provide a graphene dispersion which can uniformly distribute a conductive agent, an active material, and the like when coated for forming an electrode, and which is suitable for producing battery electrodes for highly efficient lithium ion batteries and the like, without adversely affecting the resistance value, etc., of the electrode itself while maintaining high output characteristics and cycle characteristics.

[0013] The objects and advantages of the invention will be realized and obtained by means of the elements and combinations particularly pointed out in the claims. Both the foregoing general description and the following detailed description are exemplary and explanatory but are not restrictive of the invention as claimed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The following describes in detail the embodiments of the present invention. However, please note that the technical scope of the present invention is not limited to the embodiments described in detail below, but extends to the inventions described in the claims and their equivalents. The present invention can be implemented based on the contents disclosed in this specification and common technical knowledge in the relevant field (including design matters and obvious matters).

[0015] Graphene Dispersion for Battery Electrodes The graphene dispersion for battery electrodes of the present invention has a viscosity of at least 15 m. 2 / g or more 70m 2 The graphene material has a BET specific surface area of ​​less than 100 nm / g, a peak height ratio of the 2D band to the G band (2D / G) measured by Raman spectroscopy of 0.3 to less than 0.9, and a total content of Fe, Co, and Ni of less than 5,000 ppm; a dispersant; and a solvent.

[0016] Graphene Materials The graphene material used in the present invention is a thin flake in which graphene sheets each having a thickness of one carbon atom are accumulated in a layered form, and each layer is made up of hexagonal cells made of carbon atoms. 2 / g or more 70m 2 / g, the peak height ratio of the 2D band to the G band (2D / G) measured by Raman spectroscopy is 0.3 or more and less than 0.9, and the total content of Fe, Co, and Ni is less than 5000 ppm.

[0017] The graphene material is at least one type (either a single type or a mixture of two or more types, the same applies hereinafter) selected from raw graphene such as scaly graphite particles, flaky graphite particles, spherical graphite particles, expanded graphite particles, exfoliated expanded graphite particles, exfoliated scaly graphite particles, and graphene particles, and is obtained by subjecting the raw graphene to a pulverization / classification operation or a demetallization operation as necessary, and is graphene having the specific properties described above.

[0018] The raw graphene to be used may be one produced by a method such as a chemical vapor deposition method, a pyrolysis method, a mechanical exfoliation method, a chemical treatment method, or a supercritical fluid exfoliation method, and may further be one that has been subjected to a pulverization operation, a classification operation, or a demetallization operation, as necessary.

[0019] Examples of commercially available scaly graphite particles that can be used include SP-270, J-SP-α, JB-5 (all manufactured by Nippon Graphite Co., Ltd.), FT-7J (manufactured by Fuji Graphite Co., Ltd.), and NOCSP. Examples of commercially available flaky graphite particles that can be used include CMX-40, UP-5N, and UP-50N (all manufactured by Nippon Graphite Co., Ltd.). Examples of commercially available spherical graphite particles include CGB-6, CGB-20, and CGC-50 (all manufactured by Nippon Graphite Co., Ltd.). Examples of the expandable graphite particles that can be used include commercially available products such as FS-5 (manufactured by Higashi Nippon Carbon Co., Ltd.).

[0020] Examples of the grinding operation that can be applied when grinding the graphene material include dry grinding using a pin mill, a pulverizer, a hammer mill, a jet mill, a ball mill, a Henschel mixer, an attritor, or the like, and wet grinding using an ultrasonic disperser, a disperser, a homomixer, a rotation-revolution mixer, a planetary mixer, a high-pressure homogenizer, a paint conditioner, colloid mills, a bead mill, a cone mill, a wet jet mill, a thin film rotary type high-speed mixer, or the like.

[0021] As the classification operation that can be applied, a device utilizing gravity, inertial force, or centrifugal force, or a device utilizing a filter can be used in a dry method or a wet method. Applicable demetallization procedures include one or more of an acid treatment, a base treatment, a calcination treatment in an inert atmosphere, and the like, which may be combined as necessary.

[0022] In the present invention, it is particularly preferable to carry out a pulverization operation, a classification operation, and a demetallization operation in order to maintain the output characteristics and cycle characteristics of a lithium ion battery or the like at a high level and not to adversely affect the resistance value and the like of the electrode itself.

[0023] The BET specific surface area of ​​the graphene material used in the present invention is 15 m 2 / g or more 70m 2 / g, preferably less than 25m 2 / g over 70m 2 / g, more preferably less than 25m 2 / g over 50m 2 / g.

[0024] In order to obtain a graphene material having the above BET specific surface area, grinding and classification are performed as necessary. This allows the BET specific surface area to be adjusted to a suitable range, resulting in a preferable property for a dispersion for battery electrodes. 2 If the viscosity is more than 1 / g, the viscosity of the dispersion becomes high, making it difficult to continue the production, and the conductive agent, active material, etc. cannot be uniformly applied when forming an electrode. In the present invention (including the examples described later), the "BET specific surface area" is measured by a BET single point method. An example of a measuring device is Macsorb (manufactured by Mountec Co., Ltd.).

[0025] The graphene material used in the present invention has a peak height ratio (2D / G) of the 2D band and the G band specific to graphene, as measured by Raman spectroscopy, of 0.3 or more and less than 0.9, preferably 0.3 or more and less than 0.7, more preferably 0.3 or more and less than 0.5, and even more preferably 0.35 or more and less than 0.5. Here, the 2D band has a peak height ratio of 2680 cm -1 ~2730cm -1 The G band is scattered light due to the CH stretching motion of -1 ~1620cm -1 This scattered light is due to the C=C stretching motion of the aromatic ring.

[0026] In order to obtain a graphene material having the above-mentioned peak height ratio (2D / G) of the Raman spectrum, grinding and classification are performed as necessary. This allows the peak height ratio (2D / G) to be adjusted to a suitable range, resulting in a preferable property as a dispersion for battery electrodes. When the peak height ratio (2D / G) of the graphene material is 0.9 or more, the viscosity of the dispersion becomes high, making it difficult to continue producing the dispersion, and it becomes impossible to uniformly coat the conductive agent, active material, etc. when forming an electrode. A Raman spectrometer is used as a measuring device for the Raman spectrum.

[0027] The total content of Fe, Co, and Ni in the graphene material used in the present invention is less than 5000 ppm, preferably less than 3000 ppm, and more preferably less than 1000 ppm.

[0028] In order to obtain a graphene material having the above Fe, Co, and Ni contents, a demetallization operation is performed as necessary. This allows the Fe, Co, and Ni contents to be adjusted to a suitable range, resulting in a preferable property as a dispersion for a battery electrode. If the total Fe, Co, and Ni content of the graphene material is 5000 ppm or more, Fe, Co, and Ni will dissolve in the electrolyte during charging and discharging of the battery, deteriorating the cycle characteristics, and making it impossible to achieve a long battery life.

[0029] In the present invention (including the examples described later), the total content of Fe, Co, and Ni in the graphene material is measured by ashing the graphene material, extracting it with nitric acid, quantifying Fe, Co, and Ni with a measuring device, and summing them up. An example of the measuring device is an ICP optical emission spectrometer SPECTROBLUE TI (manufactured by Hitachi High-Tech Corporation).

[0030] In the present invention, when the graphene dispersion is further diluted with a solvent to obtain a dispersion having a graphene material concentration of 50 ppm, the absorbance of the dispersion at 550 nm is preferably 1.30 or more and 3.0 or less. The absorbance at 550 nm corresponds to the dispersion of the graphene material, and if it is 1.30 or more, it is preferable because it indicates that the dispersion of the graphene material has progressed sufficiently, but if it exceeds 3.0, it is not preferable because the graphene material is significantly pulverized. In addition, the ratio of the 380 nm absorbance / 780 nm absorbance of the diluted dispersion also corresponds to the dispersion of the graphene material, and if it is 1.20 or more, it is preferable because it indicates that each graphene sheet is peeled off without being broken and is well dispersed.

[0031] In the present invention, the graphene material is mixed with a dispersion medium and a dispersant to form a graphene dispersion. The graphene dispersion of the present invention is a slurry in which graphene is uniformly dispersed and has a low viscosity. The content of the graphene material in the graphene dispersion can be set to a suitable content depending on the application.

[0032] For example, when the graphene dispersion in a slurry state is used as a conductive material, an electrode slurry for a secondary battery, an electrode for a secondary battery, or the like, the content of the graphene material in the graphene dispersion is preferably 1 to 20 mass%, more preferably 1 to 15 mass%, further preferably 3 to 10 mass%, and particularly preferably 4 to 7 mass%, relative to the total amount of the graphene dispersion, from the viewpoint of enabling a conductive agent, an active material, and the like to be uniformly distributed when coating for forming an electrode.

[0033] By making the content of the graphene material in the graphene dispersion 1% by mass or more, the amount of solvent carried over during blending of the electrode slurry is reduced, which increases the degree of freedom in blending design and ensures sufficient conductivity. On the other hand, by making the content of the graphene material in the graphene dispersion 20% by mass or less, the stability and good conductivity of the dispersion can be ensured.

[0034] When the dispersion medium is water or a water-soluble solvent, the dispersant used in the present invention is preferably at least one of polyvinylpyrrolidone, carboxymethylcellulose and its salts (alkali metal salts such as Li, Na, and K), cellulose nanofibers, polyvinyl butyral, acrylic polymers, styrene acrylic polymers, etc. Among these, polyvinylpyrrolidone, carboxymethylcellulose and its salts, cellulose nanofibers, and polyvinyl butyral are particularly preferred.

[0035] When the dispersion medium is non-aqueous, at least one of polyvinylpyrrolidone, polyvinyl butyral, acrylic polymer, styrene acrylic polymer, polyvinylidene fluoride, etc. is suitable. When the dispersion medium is a low polarity solvent such as a paraffinic or naphthenic hydrocarbon, the acrylic polymer preferably contains a cationic group, and the amine value of the acrylic polymer is preferably 13 mgKOH / g or less. In addition, it is more preferable that the dispersion medium does not contain toluene or xylene from the viewpoint of dispersion stability.

[0036] The content of the dispersant in the present invention can be set to a suitable content depending on the application. For example, when used in a conductive slurry, a secondary battery electrode slurry, a secondary battery electrode, etc., the content of the dispersant is preferably 3 to 50 parts by mass, more preferably 5 to 30 parts by mass, further preferably 8 to 25 parts by mass, and particularly preferably 10 to 20 parts by mass relative to 100 parts by mass of the graphene material, from the viewpoint of exerting the effects of the present invention and maintaining high dispersibility of the graphene material without deteriorating other performances.

[0037] By setting the content of the dispersant to 3 parts by mass or more relative to 100 parts by mass of the graphene material, sufficient dispersibility can be ensured, while by setting the content of the dispersant to 50 parts by mass or less relative to 100 parts by mass, stability and good electrical conductivity of the graphene dispersion can be ensured.

[0038] In the graphene dispersion of the present invention, an aqueous dispersion medium or a non-aqueous dispersion medium is used. The aqueous dispersion medium in one embodiment of the graphene dispersion of the present invention is water (e.g., purified water, distilled water, pure water, ultrapure water, tap water, ion-exchanged water, etc.). In addition, an organic water-soluble solvent can be used as the aqueous dispersion medium.

[0039] Examples of the water-soluble solvent that can be used include ethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, dipropylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 2,3-butanediol, 1,3-butanediol, 1,4-butanediol, 1,2-pentanediol, 1,5-pentanediol, 2,5-hexanediol, 3-methyl-1,3-butanediol, 2-methylpentane-2,4-diol, 3-methylpentane-1,3,5-hexanediol, 2-methylpentane-2,4-diol, 2 ...2,4-diol, 2-methylpentane-2,4-diol, 2-methylpentane-2,4-diol, 2-methylpentane-2,4-diol, 2-methylpentane-2,4-diol, 2-methylpentane-2,4-diol, 2-methylpentane-2,4-diol, 2-methylpentane-2,4-diol, 2-methylpentane-2,4-diol, 2-methylpentane-2,4-diol, 2-methyl triol, 1,2,3-hexanetriol, and other alkylene glycols; polyethylene glycol, polypropylene glycol, and other polyalkylene glycols; glycerols, such as glycerol, diglycerol, and triglycerol; lower alkyl ethers of glycols, such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, and diethylene glycol mono-n-butyl ether; N-methyl-2-pyrrolidone, and 1,3-dimethyl-2-imidalidinone.

[0040] As the water-soluble solvent serving as the dispersion medium, for example, water-soluble solvents such as amides such as N,N-dimethylacetamide and N,N-dimethylformamide, and ketones such as acetone can be used alone or in combination. Water may be mixed with the water-soluble solvent.

[0041] The content of these water-soluble solvents varies depending on the solid content of the dispersion. From the viewpoint of improving the wettability of the graphene material and the mixability of the slurry, the content is preferably 0.1 to 7 mass % and more preferably 0.1 to 5 mass % relative to the total amount of the dispersion.

[0042] As the non-aqueous dispersion medium in another embodiment of the graphene dispersion for a battery electrode of the present invention, a non-aqueous solvent can be used.

[0043] Examples of non-aqueous solvents that can be used in the present invention include γ-butyrolactone, acetone, methyl ethyl ketone, hexane, heptane, octane, 2-heptanone, cycloheptanone, cyclohexanone, cyclohexane, methylcyclohexane, ethylcyclohexane, methyl-n-pentyl ketone, methyl isobutyl ketone, methyl isopentyl ketone, ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, ethylene glycol monoacetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, and diethylene glycol monoacetate. , diethylene glycol diethyl ether, propylene glycol monoacetate, dipropylene glycol monoacetate, propylene glycol diacetate, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, cyclohexyl acetate, ethyl 3-ethoxypropionate, dioxane, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate,

[0044] Anisole, ethyl benzyl ether, cresyl methyl ether, diphenyl ether, dibenzyl ether, phenetole, butyl phenyl ether, benzene, ethyl benzene, diethyl benzene, pentyl benzene, isopropyl benzene, toluene, xylene, cymene, mesitylene, methanol, ethanol, isopropanol, butanol, methyl monoglycidyl ether, ethyl monoglycidyl ether, butyl monoglycidyl ether, phenyl monoglycidyl ether, methyl diglycidyl ether, ethyl diglycidyl ether, butyl diglycidyl ether, phenyl diglycidyl Ether, methylphenol monoglycidyl ether, ethylphenol monoglycidyl ether, butylphenol monoglycidyl ether, mineral spirits, 2-hydroxyethyl acrylate, tetrahydrofurfuryl acrylate, 4-vinylpyridine, N-methyl-2-pyrrolidone, 2-ethylhexyl acrylate, 2-hydroxyethyl methacrylate, hydroxypropyl methacrylate, glycidyl methacrylate, neopentyl glycol diacrylate, hexanediol diacrylate, trimethylolpropane triacrylate, methacrylate, methyl methacrylate,

[0045] Examples of the solvent include one selected from the group consisting of styrene, perfluorocarbon, hydrofluoroether, hydrochlorofluorocarbon, hydrofluorocarbon, perfluoropolyether, N,N-dimethylformamide, N,N-dimethylacetamide, dioxolane, cyclohexanol acetate, dipropylene glycol dimethyl ether, propylene glycol diacetate, dipropylene glycol methyl-n-propyl ether, dipropylene glycol methyl ether acetate, 1,4-butanediol diacetate, 1,3-butylene glycol diacetate, 1,6-hexanediol diacetate, various silicone oils, various naphthene-based solvents, various paraffin-based solvents, and various isoparaffin-based solvents, or solvents containing two or more of these solvents.

[0046] Of these solvents, preferred are methyl ethyl ketone, cyclohexanone, toluene, xylene, N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dioxolane, butyl butyrate, and isoparaffin-based solvents.

[0047] In the present invention, when a non-aqueous solvent is used as a dispersion medium, the water content of the graphene dispersion is preferably 5000 ppm or less, more preferably 3000 ppm or less, and even more preferably 1000 ppm or less. The non-aqueous solvent used preferably has a low water content.

[0048] The graphene dispersion of the present invention may further contain conductive particles made of graphite-type carbonaceous material in addition to the graphene material described above, in order to further exert the effects of the present invention. Examples of conductive carbon particles that can be used include carbon black particles such as acetylene black and ketjen black, carbon nanofibers such as single-walled carbon nanotubes having a structure in which a graphene sheet is rolled into a cylindrical shape, and multi-walled carbon nanotubes having a structure in which multiple cylindrical graphene sheets with different cylindrical diameters are inserted.

[0049] The specific gravity difference with the graphene material is ±0.2g / cm 3 Conductive carbon particles having a specific gravity within this range are preferably used. A graphene dispersion using such conductive carbon particles is unlikely to separate due to a difference in specific gravity when stored as it is or as an electrode slurry containing the conductive carbon particles.

[0050] The average outer diameter of the usable carbon nanofibers is preferably 1 nm or more and 90 nm or less, more preferably 3 nm or more and 30 nm or less, and even more preferably 3 nm or more and 15 nm or less, from the viewpoints of electrical conductivity and stability. Here, the average outer diameter of the carbon nanofibers refers to the arithmetic mean value of the outer diameters of a sufficient number n measured using an image of a transmission electron microscope at a magnification of 100,000 times or more.

[0051] The content of the conductive carbon particles to be blended when the graphene dispersion of the present invention is used for a battery electrode can be set to a suitable content depending on the application and from the viewpoint of further maximizing the effects of the present invention. For example, when the graphene dispersion is used for a conductive slurry, a secondary battery electrode slurry, a secondary battery electrode, etc., the content of the conductive carbon particles is preferably 0.5 to 10 mass %, more preferably 0.5 to 7 mass %, and particularly preferably 0.5 to 5 mass %, based on the total amount of the graphene dispersion.

[0052] The graphene dispersion for battery electrodes of the present invention can be produced, for example, by adding at least the above-mentioned graphene material, dispersant, and dispersion medium, carrying out a stirring and mixing step, and then carrying out a dispersing step.

[0053] The dispersion step in the production of the graphene dispersion can be carried out by dispersion treatment using, for example, an ultrasonic disperser, a disperser, a homomixer, a rotation-revolution mixer, a Henschel mixer, a planetary mixer, or other mixer; a (high-pressure) homogenizer, a paint conditioner, colloid mills, a media-type disperser such as a bead mill, a cone mill, a ball mill, a sand mill, an attritor, a pearl mill, or a coball mill; a media-less disperser such as a wet jet mill or a thin film rotary high-speed mixer; or other dispersing devices such as a roll mill, but is not limited to these. From the viewpoints of stability and dispersion efficiency, preferred dispersing devices are a thin film rotary type high speed mixer and a bead mill.

[0054] In the production of the graphene dispersion, it has been confirmed from the examples described below that as the dispersion in the dispersion step (for example, ultrasonic disperser) progresses, the graphene material is crushed and the blackness (absorbance) increases. The crushing of the graphene material is dominated by delamination of the layered graphene material rather than fracture of the graphene sheet surface itself. Since the graphene sheet surface itself is not fractured, when a battery electrode is produced from the graphene dispersion, it becomes easier to form and maintain an electrically conductive path or a thermally conductive path.

[0055] The graphene dispersion of the present invention can be used to prepare a slurry for battery electrodes with excellent flowability. In terms of obtaining fluidity of the electrode slurry in the battery electrode slurry, the graphene dispersion used preferably has a viscosity value (mPa·s) at 25°C at 10 rpm using an E-type rotational viscometer [TV-25 (manufactured by Toki Sangyo Co., Ltd.) rotor (1°34'×R24 mm)] of 3 to 700, more preferably 5 to 300, and even more preferably 5 to 200. Similarly, the viscosity value (mPa·s) at 25°C at 1 rpm is preferably 30 to 7000, more preferably 50 to 3000, and even more preferably 50 to 2000.

[0056] In addition, the graphene dispersion of the present invention is preferably a non-aqueous composition using a non-aqueous solvent in order to obtain the fluidity of a slurry for a battery electrode prepared using the graphene dispersion. The water content (ppm) is preferably 5000 or less, more preferably 3000 or less, 2500 or less, 2000 or less, 1800 or less, 1600 or less, 1400 or less, 1200 or less, and further preferably 1000 or less. The water content contained in the graphene dispersion can be measured by a Karl Fischer moisture meter (coulometric titration method).

[0057] The graphene dispersion of the present invention can be suitably used as an electrode slurry, such as a positive electrode slurry or a negative electrode slurry, for a secondary battery such as a lithium ion battery, by further adding various components such as conductive particles. The graphene dispersion of the present invention is a dispersion in which graphene materials and the like are uniformly dispersed and has a low viscosity, so that conductive materials and active materials can be uniformly distributed when the graphene dispersion is applied to form an electrode. Moreover, when the graphene dispersion of the present invention is used in a lithium ion battery electrode, the Li + The high C rate characteristics and cycle characteristics of lithium-ion batteries can be maintained to a high degree without adversely affecting the flow of ions or the resistance of the electrodes.

[0058] In addition, in an electrode slurry using conductive particles together with the graphene dispersion of the present invention, it is presumed that the graphene material has many exposed c-axis faces (edges), so that there is a lot of contact between the conductive particle surface and the c-axis faces (edges), and a coating film obtained from this electrode slurry is expected to have a low resistance value. In particular, in an electrode slurry using fibrous conductive particles such as carbon nanotubes together with a graphene dispersion, many c-axis faces (edges) of the graphene material come into contact with the conductive particles, and in addition to the above-mentioned decrease in resistance value, it is expected that ions liberated from the active material described later will enter and exit the gaps around the contact parts between the fibrous conductive particles and the c-axis faces (edges) of the dispersed graphene particles, and that they will be more likely to be retained.

[0059] <Positive electrode slurry> The positive electrode slurry of the present invention is characterized by containing the graphene dispersion having the above-mentioned configuration and at least a positive electrode active material. As the positive electrode active material, a material that allows lithium ions to reversibly enter and leave the positive electrode of a lithium ion battery can be used.

[0060] Examples of the positive electrode active material include composite oxides of lithium and transition metals such as lithium-nickel composite oxide, lithium-cobalt composite oxide, lithium-manganese composite oxide, lithium-nickel-manganese composite oxide, lithium-nickel-cobalt composite oxide, lithium-nickel-aluminum composite oxide, lithium-nickel-manganese-cobalt composite oxide, lithium-nickel-manganese-aluminum composite oxide, lithium-nickel-manganese-aluminum composite oxide, and lithium-nickel-cobalt-manganese-aluminum composite oxide; transition metal sulfides such as TiS2, FeS, and MoS2; MnO, V---2O5, and V6O 13 , transition metal oxides such as TiO2, and olivine-type lithium phosphate.

[0061] The olivine-type lithium phosphate contains, for example, at least one element selected from the group consisting of Mn, Cr, Co, Cu, Ni, V, Mo, Ti, Zn, Al, Ga, Mg, B, Nb, and Fe, as well as lithium, phosphorus, and oxygen. These compounds may have some elements partially substituted with other elements in order to improve their properties. The positive electrode active material is preferably a lithium-nickel composite oxide, more preferably a lithium-nickel composite oxide represented by the formula: LiNi X M1 Y M2 Z O2 (M1 and M2 are at least one metal element selected from the group consisting of Al, B, alkali metals, alkaline earth metals, and transition metals; 0.8≦X≦1.0, 0≦Y≦0.2, 0≦Z≦0.2), or lithium phosphate. These positive electrode active materials may be used alone or in combination of two or more.

[0062] In the positive electrode slurry of the present invention, the content of the positive electrode active material is preferably 50 to 70 mass %, and more preferably 50 to 63 mass %, based on the total amount of the positive electrode slurry in order to ensure the battery capacity and the fluidity of the slurry. The content of the graphene material in the positive electrode slurry is preferably 0.05 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, and even more preferably 0.05 to 1 part by mass, relative to 100 parts by mass of the positive electrode active material.

[0063] The positive electrode slurry of the present invention contains the graphene dispersion and the positive electrode active material having the above-mentioned configuration, and may contain a solid electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a dry polymer electrolyte, a gel polymer electrolyte, or a quasi-solid electrolyte, as necessary.

[0064] <Slurry for negative electrode> The negative electrode slurry of the present invention is characterized by containing the graphene dispersion having the above-mentioned configuration and at least a negative electrode active material. As the negative electrode active material, for example, metal oxide-based active material particles, silicon-based active material particles, and spherical graphite can be used, and in particular, metal oxide-based negative electrode active material particles can be preferably used.

[0065] For example, titanium oxide can be used as the metal oxide-based negative electrode active material particles. The titanium oxide is not particularly limited as long as it can absorb and release lithium, but for example, spinel-type lithium titanate, ramsdellite-type lithium titanate, titanium-containing metal composite oxide, titanium dioxide (TiO2(B)) having a monoclinic crystal structure, and anatase-type titanium dioxide can be used.

[0066] Spinel-type lithium titanate includes Li 4+x Ti5O 12 (x varies in the range of 0≦x≦3 depending on the charge / discharge reaction). Ramsdellite-type lithium titanate includes Li 2+y Ti3O7 (where y varies in the range of 0≦y≦2 depending on the charge / discharge reaction). TiO2(B) and anatase-type titanium dioxide include Li 1+z TiO2 (z changes in the range of -1≦z≦0 depending on the charge / discharge reaction).

[0067] Examples of titanium-containing metal composite oxides include metal composite oxides containing Ti and at least one element selected from the group consisting of P, V, Sn, Cu, Ni, and Fe. Examples of metal composite oxides containing Ti and at least one element selected from the group consisting of P, V, Sn, Cu, Ni, and Fe include TiO2-P2O5, TiO2-V2O5, TiO2-P2O5-SnO2, and TiO2-P2O5-MeO (Me is at least one element selected from the group consisting of Cu, Ni, and Fe).

[0068] Such a metal composite oxide preferably has a microstructure with low crystallinity, in which a crystalline phase and an amorphous phase coexist, or in which an amorphous phase exists alone, which can further improve cycle performance.

[0069] In the negative electrode slurry of the present invention, the content of the negative electrode active material is preferably 30 to 60 mass %, and more preferably 35 to 55 mass %, based on the total amount of the negative electrode slurry in order to ensure the battery capacity and the fluidity of the slurry.

[0070] The content of the graphene dispersion for a battery electrode having the above configuration is preferably 0.05 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, and even more preferably 0.05 to 1 part by mass, based on the amount of the graphene material, per 100 parts by mass of the negative electrode active material.

[0071] The negative electrode slurry of the present invention contains the graphene dispersion and the negative electrode active material having the above-mentioned configuration, and may contain, as necessary, a solid electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a dry polymer electrolyte, a gel polymer electrolyte, or a quasi-solid electrolyte.

[0072] Each of the positive electrode slurry and the negative electrode slurry obtained above preferably further contains a binding material (binder).

[0073] Examples of the binder that can be used include fluororesins such as polyimide resins, polyvinylidene fluoride (PVdF), polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinyl ether copolymers, polyolefin resins such as polyethylene and polypropylene, polyvinylpyrrolidone, polyvinyl alcohol, styrene-butadiene rubber (SBR), and acrylic resins. Two or more of these binders may be mixed together for use.

[0074] The amount of these binders is preferably 0.05 to 5 parts by mass, more preferably 0.1 to 4.5 parts by mass, and even more preferably 1.5 to 4.5 parts by mass, relative to 100 parts by mass of the active material in the electrode slurry for a secondary battery, from the viewpoints of adhesion to the current collector foil, and battery capacity and charge / discharge characteristics after cell formation.

[0075] An aqueous or non-aqueous solvent may be further added to the electrode slurry depending on the properties of each slurry. Examples of the solvent include water (purified water, ion-exchanged water, distilled water, ultrapure water, etc.), aromatic solvents, alcohols, polyhydric alcohols, ether solvents, glycol ether solvents, ester solvents, amine solvents, amide solvents, heterocyclic solvents, sulfoxide solvents, sulfone solvents, etc. These solvents may be used alone or in combination of two or more.

[0076] The amount of these solvents is preferably 0.5 to 80 mass %, more preferably 1 to 70 mass %, based on the total amount of the electrode slurry for secondary batteries, from the viewpoint of the need to finish the electrode slurry to an appropriate viscosity when it is applied.

[0077] Furthermore, in addition to the graphene dispersion for battery electrodes, each active material, binder, and solvent, the electrode slurry may appropriately contain a leveling agent, a solid electrolyte, a preservative, and the like within a range that does not impair the effects of the present invention.

[0078] The slurry for electrodes of secondary batteries configured in this manner can be prepared by mixing the graphene dispersion for battery electrodes, each active material for a positive electrode or a negative electrode of a secondary battery, a binder, a solvent, etc. For example, a biaxial kneader can be used for mixing.

[0079] By using the electrode slurry obtained as described above, an electrode for a secondary battery can be obtained. The electrode slurry for the positive electrode or the negative electrode is applied onto a current collector, which is a conductive member of a lithium ion secondary battery, and then dried to obtain a desired positive electrode or negative electrode for the lithium ion secondary battery. That is, by using each electrode slurry of the present invention, a secondary battery electrode that realizes high output and battery performance that can withstand repeated charging and discharging for a long period of time can be obtained.

[0080] The material and shape of the current collector used as the base material of the electrode are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. For example, the material of the current collector can be metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel. In addition, as for the shape, a flat foil is generally used, but a roughened surface, a perforated foil, or a mesh-shaped current collector can also be used.

[0081] The electrode slurry is applied to a current collector and dried to prepare an electrode. A known method can be used to apply the electrode slurry. Specific examples include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic coating. After application, rolling treatment using a lithographic press or a calendar roll may be performed.

[0082] The electrode slurry can be dried using natural drying, a blower dryer, a hot air dryer, an infrared heater, a far infrared heater, or the like. The thickness of the electrode formed on the current collector is generally 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.

[0083] The positive electrode or negative electrode slurry of the present invention uses the graphene dispersion having the above-mentioned characteristics, and therefore the conductive material and active material can be uniformly distributed when applied to form an electrode, and the slurry has excellent coatability and stability without adversely affecting the high C rate (high output) characteristics and cycle characteristics.

[0084] (Secondary batteries, lithium-ion secondary batteries) A secondary battery is usually composed of a positive electrode, a negative electrode, an electrolyte, a non-aqueous solvent, and a separator that is provided as necessary, and can be formed in various shapes according to the purpose of use, such as a paper type, a cylindrical type, a button type, a laminated type, etc. For the positive electrode or negative electrode of a lithium ion secondary battery, an electrode prepared by coating the above-mentioned electrode slurry can be used. The use of the present invention in a lithium ion secondary battery will be described below.

[0085] As the positive electrode, an electrode prepared by coating a current collector with the above-mentioned positive electrode slurry containing a positive electrode active material and drying the coating can be used. As the negative electrode, an electrode prepared by coating a current collector with the above-mentioned negative electrode slurry containing a negative electrode active material and drying the coating can be used.

[0086] As the electrolyte, various conventionally known electrolytes capable of moving ions can be used. For example, those containing lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be used, but are not limited thereto. The electrolyte is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.

[0087] Examples of non-aqueous solvents include, but are not limited to, carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.

[0088] The structure of the lithium ion secondary battery is not particularly limited, but it is usually composed of a positive electrode, a negative electrode, and a separator that is provided as necessary, and can be in various shapes according to the purpose of use, such as a paper type, a cylindrical type, a button type, a coin type, a laminated type, etc. Examples of the separator include polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and these that have been subjected to a hydrophilic treatment. A secondary battery such as a lithium ion secondary battery that is constructed using an electrode formed using the electrode slurry of the present invention has high output and battery performance that can withstand repeated charging and discharging over a long period of time. EXAMPLES

[0089] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.

[0090] [Preparation of graphene material] Using the raw graphene shown in Table 1 below, graphene materials for use in graphene dispersions were prepared by applying various additional operations. The raw graphene used was expanded graphite GR-10 (manufactured by Nippon Graphite Co., Ltd.), expanded graphite FS5 (manufactured by East Japan Carbon Co., Ltd.), exfoliated graphite UP-5N (manufactured by Nippon Graphite Co., Ltd.), Graphene powder GP (manufactured by 2D Materials Pte. Ltd.), and CVD graphene. CVD graphene is a powdered graphene material obtained by using chemical vapor deposition (CVD) to flow methane gas in an atmosphere at 980°C to form a film on copper foil formed on a sapphire substrate, removing the copper foil by etching, and then pulverizing the film.

[0091] Additional operations for the raw graphene were appropriately selected from the demetallization operation, the crushing operation, and the classification operation, and were carried out in the above order. The applied operations are indicated by ○ in Table 1. Details of each operation are as follows. After each operation, the BET specific surface area (m 2 Table 1 shows the 2D / G ratio of the peak intensity of the Raman spectrum, and the total content of Fe, Co, and Ni (ppm).

[0092] [Table 1]

[0093] [Demetallization operation] 10 parts by mass of raw graphene was added to 90 parts by mass of a solvent made by mixing 10% by mass of ethanol in purified water, and nitric acid was added thereto to adjust the pH to 2.5 or less. The liquid temperature was controlled at 40°C, and the mixture was stirred for 2 hours and then filtered. The filtered material was put into 90 parts by mass of purified water, redispersed, and filtered, and this washing operation was repeated until the pH of the filtrate became 5 or more.

[0094] [Crushing Operation] Two parts of raw graphene were added to 98 parts of a solvent made by mixing 10% by mass of ethanol in purified water, and the mixture was homogenized using a disperser, and then pulverized in a 1200W continuous ultrasonic disperser by circulating the mixture with a pump while cooling so that the processing time (residence time) in the ultrasonic disperser was 30 minutes. After that, the solvent was removed by suction filtration, and powdered graphene material was obtained by freeze-drying. When the grinding operation was not performed, the graphene powder material was obtained by simply freeze-drying the raw graphene.

[0095] [Classification operation] The raw graphene, which had / had not undergone demetallization and / or pulverization, was classified at a classification point of 2 μm using an Elbow Jet Classifier (manufactured by Matsubo Corporation), and the fine particle powder was collected to obtain powdered graphene material.

[0096] [Preparation and evaluation of graphene dispersions] The obtained graphene material, dispersant, and solvent were charged into a dispersing device (a bead mill using zirconia beads of φ0.3 mm) in the blending composition shown in Table 2, and dispersed by a dispersion treatment under conditions of a peripheral speed set to 10 m / s and a residence time of 30 minutes, thereby obtaining graphene dispersions of Examples 1 to 24 and Comparative Examples 1 to 9. The obtained graphene dispersion was evaluated for its dispersion characteristics and battery characteristics. The battery characteristics were evaluated after forming an electrode slurry, coating the electrode, and forming a coin cell, as described below.

[0097] [Raman spectrum] The graphene dispersion was applied onto a current collector with an applicator, and the coating surface was dried at 80°C. The coating surface was mapped over an area of ​​100 μm square using a Raman spectrometer DXR2xi (manufactured by Thermo Fisher Scientific), and the peak top position of the Raman spectrum was measured.

[0098] [Low shear / high shear viscosity] Using an E-type rotational viscometer (Toki Sangyo Co., Ltd., TV-25; rotor (1°34' × R24mm)), the viscosity measured at 25°C at 1 rpm (mPa s) was evaluated as the low shear viscosity, and the viscosity measured at 25°C at 10 rpm (mPa s) was evaluated as the high shear viscosity. 〔moisture〕 The graphene dispersion was evaluated using a coulometric Karl Fischer moisture meter (MKC-610, manufactured by Kyoto Electronics Manufacturing Co., Ltd.).

[0099] [550nm absorbance] The graphene dispersion was diluted with N-methyl-2-pyrrolidone (NMP) to give a graphene material concentration of 50 ppm to prepare a dispersion, and the absorbance of the dispersion at 550 nm was measured with a spectrophotometer (U-3300, manufactured by Hitachi, Ltd.) using a cell with an optical path length of 10 mm.

[0100] [380nm / 780nm absorbance ratio] The graphene dispersion was diluted with N-methyl-2-pyrrolidone (NMP) to give a graphene material concentration of 50 ppm to prepare a dispersion. Using a cell with an optical path length of 10 mm, the absorbance at 380 nm and the absorbance at 780 nm of the dispersion were measured using the spectrophotometer. The absorbance at 380 nm was divided by the absorbance at 780 nm to calculate the absorbance ratio.

[0101] [Battery characteristic evaluation] An electrode slurry was prepared by blending 92 parts by mass of lithium iron phosphate (LiFePO4), 4 parts by mass of acetylene black (Denka Black, manufactured by Denka Co., Ltd.), 4 parts by mass of polyvinylidene fluoride (W#9700, manufactured by Kureha Corporation) and a graphene dispersion in an amount such that the graphene material was 0.1 parts by mass in NMP and mixing the materials with a planetary mixer. The obtained electrode slurry was applied to an aluminum foil current collector having a thickness of 25 μm with an applicator so that the basis weight was 5 mg / cm. 2 The mixture was then dried in an oven at 80° C. to obtain an electrode sheet. The obtained electrode sheet was punched out and pressed with a press to obtain an electrode density of 2.2 g / cm 3 Three lithium batteries consisting of single-electrode coin-type cells were fabricated for each electrode sheet, with lithium metal as the counter electrode, and various battery characteristics were evaluated. A carbonate-based solvent was used as the electrolyte, and a polypropylene separator was used.

[0102] [Initial discharge capacity] The theoretical capacity of lithium iron phosphate was set to 170 mAh / g, and the discharge capacity in the second cycle after the initial charge / discharge was evaluated for three coin-type cells, and the average value was taken as the initial discharge capacity. [5C charge / discharge capacity retention rate] As a resistance test for high-power charging and discharging, the above-mentioned initial discharge capacity was evaluated for three coin-type cells, and then the discharge capacity was evaluated in the same manner as described above with a C rate of 5C, and the percentage of the discharge capacity relative to the theoretical capacity was calculated as an average value. [Capacity retention rate after 30 cycles] As a durability test for repeated charge and discharge, the 5C charge and discharge capacity retention rate was evaluated for three coin-type cells, and then a cycle of charging and discharging at 1C was repeated in an environment of 25°C, the discharge capacity after 30 cycles was evaluated, and the percentage of the discharge capacity relative to the theoretical capacity was calculated as an average value.

[0103] [Table 2]

[0104] As is clear from the evaluation results in Tables 1 and 2, the electrodes prepared from the electrode slurries using the graphene dispersions of Examples 1 to 24 within the scope of the present invention exhibited highly excellent characteristics in terms of initial capacity, output characteristics, and cycle characteristics. In contrast, the electrodes prepared from the electrode slurries using the graphene dispersions of Comparative Examples 1 to 9 outside the scope of the present invention could not satisfy the above characteristics. [Industrial Applicability]

[0105] The graphene dispersion of the present invention has excellent stability and conductive performance, and is useful as a material for fuel cells, various electrodes, electromagnetic wave shielding materials, conductive resins, members for field emission displays, building members, coating members, paint members such as ship bottom paints, and the like. The graphene dispersion of the present invention can be used in an electrode slurry suitable for producing electrodes (positive and negative electrodes) of lithium ion secondary batteries, in particular. An electrode produced from an electrode slurry using the graphene dispersion of the present invention can achieve excellent battery performance capable of withstanding high-output charge / discharge and repeated charge / discharge over a long period of time.

Claims

1. At least 15 meters 2 / g or more 70m 2 / g, a peak height ratio (2D / G) of a 2D band to a G band measured by Raman spectroscopy is 0.3 or more and less than 0.9, and a total content of Fe, Co and Ni is less than 5000 ppm; a dispersant; and a solvent.

2. 2. The graphene dispersion according to claim 1, wherein the dispersant is at least one selected from the group consisting of polyvinylpyrrolidone, polyvinyl butyral, carboxymethyl cellulose and salts thereof, and cellulose nanofibers.

3. 3. The graphene dispersion according to claim 1, wherein the graphene dispersion has a moisture content of 5000 ppm or less.

4. 2. The graphene dispersion according to claim 1, wherein, when the graphene material is diluted with a solvent to a concentration of 50 ppm, the dispersion has an absorbance at 550 nm of 1.30 or more and a ratio of the absorbance at 380 nm / absorbance at 780 nm of 1.20 or more.

5. 2. The graphene dispersion according to claim 1, wherein a concentration of the graphene material is equal to or greater than 1% by mass and less than 20% by mass.

6. 2. The graphene dispersion according to claim 1, wherein an amount of the dispersant relative to 100 parts by mass of the graphene material is 3 parts by mass or more and less than 50 parts by mass.

7. A slurry for electrodes, prepared using at least the graphene dispersion according to any one of claims 1 to 6, and a positive electrode active material or a negative electrode active material.

Citation Information

Patent Citations

  • Alkaline battery with improved cathode

    JP2005524948A

  • Graphene structure, semiconductor device using the same, and manufacturing method therefor

    JP2013253010A

  • Graphene-dispersed liquid and preparation method thereof

    JP2014009104A

  • Crystalline graphene and method for producing crystalline graphene

    JP2014527950A

  • Graphene, method and apparatus for producing graphene

    JP2016528158A